2002
DOI: 10.1073/pnas.102691299
|View full text |Cite
|
Sign up to set email alerts
|

Iris hypoplasia in mice that lack the alternatively spliced Pax6(5a) isoform

Abstract: PAX6 is an evolutionarily conserved transcription factor that plays a critical role in vertebrate and invertebrate eye formation. Heterozygous null mutations in the PAX6 gene result in aniridia in humans and a distinct small eye syndrome in rodents. Vertebrates primarily express two alternatively spliced isoforms of Pax6 that differ by the presence or absence of exon 5a (e5A) that encodes an additional 14 aa residues within the paired domain. The e5a-containing isoform, PAX6(5a), is specific to and conserved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 36 publications
1
57
1
Order By: Relevance
“…Pax6(5a), an alternatively spliced isoform of Pax6, contains a 14-amino acid insert within the PD that considerably changes its DNA binding specificity: the canonical PD binds to DNA via its N-terminal PAI domain, whereas the Pax6(5a) PD targets DNA with the C-terminal RED domain (24). Although the Pax6(5a) isoform only constitutes up to 20% of total Pax6 transcripts, loss of Pax6(5a) in human and mouse results in distinct ocular phenotypes (24,26,27). In addition, overexpression of Pax6(5a) in cerebral cortex progenitors was observed to inhibit cell proliferation without affecting cell fate, whereas overexpression of the canonical Pax6 inhibited cell proliferation but also potently increased neurogenesis (26,28).…”
mentioning
confidence: 99%
“…Pax6(5a), an alternatively spliced isoform of Pax6, contains a 14-amino acid insert within the PD that considerably changes its DNA binding specificity: the canonical PD binds to DNA via its N-terminal PAI domain, whereas the Pax6(5a) PD targets DNA with the C-terminal RED domain (24). Although the Pax6(5a) isoform only constitutes up to 20% of total Pax6 transcripts, loss of Pax6(5a) in human and mouse results in distinct ocular phenotypes (24,26,27). In addition, overexpression of Pax6(5a) in cerebral cortex progenitors was observed to inhibit cell proliferation without affecting cell fate, whereas overexpression of the canonical Pax6 inhibited cell proliferation but also potently increased neurogenesis (26,28).…”
mentioning
confidence: 99%
“…An alternatively spliced form of PAX6, known as PAX6-5a, contains an additional 14 amino acids in the PD (2), which disrupts the N subdomain and alters DNA binding properties (13,32). Loss-of-function of Pax6-5a in mouse leads to iris-hypoplasia and also defects in the retina, lens, and cornea (33). The PDs of other genes of the Pax family, the Pax2, Pax3, and the binding sequence of Pax-5 (BSAP), and Pax6 proteins can recognize similar DNA sequences (12, 34 -39).…”
mentioning
confidence: 99%
“…Since patients with aniridia also have the PAX6-5a isoform, and Pax6-5a was found to be important in maintaining the normal structure of eyes in adult mice (33), these mutations on either end of the 5a-polypeptide insert have been used to examine the role of the PAX6-5a isoform. The results indicate that the functional properties of PAX6 and the PAX6-5a isoform are unique, and PD of PAX6 is required for the function of HD.…”
mentioning
confidence: 99%
“…Normal development of the inner retina is directly influenced by a well-elaborated spatial and temporal pattern of PAX6 expression. 1,[6][7][8][9][19][20][21] However, little is known about PAX6 expression and function in the adult mammalian retina. De Melo et al 22 showed that several homeobox genes including Pax6 are expressed in the young adult mouse retina and we recently reported continuous expression of PAX6 in the young, adult, and old normal human retina.…”
Section: Pax6 Expression and Retinal Cell Death In A Transgenicmentioning
confidence: 99%
“…4 Moreover, gain-offunction studies demonstrated that targeted expression of Drosophila and PAX6 induces ectopic eyes in Drosophila. 5 Mutations in PAX6 lead to a variety of eye abnormalities including hereditary foveal hypoplasia, optic nerve malformation, and aniridia in mice [6][7][8][9] and humans. [10][11][12][13][14][15][16][17][18] PAX6 has been studied extensively in eye and retinal development.…”
Section: Pax6 Expression and Retinal Cell Death In A Transgenicmentioning
confidence: 99%